Preparation and biochemical property of penicillin G amidase-loaded alginate and Alginate/Chitosan hydrogel beads - Nupur N.; Ashish; Mira Das D. (My University, 2025)
Background: Penicillin G amidase (PGA) (EC 3.5.1.11) are enzymes that are mainly involved in the synthesis of semi-synthetic (3-lactam antibiotics. Soluble PGA is costly and lacks long term operational stability. We revised most of the patents related to Penicillin G amidase (PGA) immobilization in the section “Recent Patents on Immobilized Penicillin G Amidase”. Objective: The aim of this work was to study comparative biochemical property of PGA enzyme immobilized in two hydro-gel beads — Ca-alginate and algi-nate+chitosan hybrid and morphologically characterised by S EM.Methods: PGA immobilized in alginate+chitosan hybrid bead shows high pH and thermal stability. Km, Vmax and Effectiveness factor (ƞ) value of free PGA were 56.19 mg/ml, 1.786 U/ml and 1, respectively. These parameters for PGA immobilized alginate beads were 64.84 mg/ml, 0.781U/ml and 0.437, respectively and for PGA immobilized alginate+chitosan hybrid beads were 87.08 mg/ml, 0.622 U/ml and 0.348, respectively. Results: Immobilized PGA on alginate+chitosan hybrid beads gave the highest thermal stability, reusability and storage stability than alginate immobilized PGA. Conclusion: The entrapment of PGA on al-ginate+chitosan hybrid beads revealed several advantages and could be used in 6APA (6-aminopenicillanic acid) production. © 2016 Bentham Science Publishers.